Two-Dimensional Zeolitic Imidazolate Framework ZIF-L: A Promising Catalyst for Polymerization; Catalysts; Vol. 12 iss. 5 - Rahaman M. A. Md Abdur; Mousavi B. Bibimaryam; Naz F. Farah; Verpoort F. V. K. Frensis Valter Kornelius (2022, 2022)
Title screen